Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Problems on algebra on alpha and beta?
If A and B are roots of the quadrctic ax^2+bx+c=0. Obtain the equation whose roots are (1/(A^2) and 1/(B^2), If in the above equation AB^2=1, Prove that a^(3)+c^(3)+abc=0
1 Answer
- POMPOMLv 510 years agoFavorite Answer
As A & B are roots of ax² + bx + c = 0, we must have
ax² + bx + c = a.(x - A)(x - B)
=> x² + (b/a)x + (c/a) = x² - (A + B)x + AB [a ≠ 0]
=> A + B = - b/a.....(1) & AB = c/a.........(2)
Now, the equations whose roots are 1/A² and 1/B² is
(x - 1/A²).(x - 1/B²) = 0
=> x² - (1/A² + 1/B²).x + (1/A²).(1/B²) = 0
=> x² - ((A² + B²)/A²B²).x + 1/A²B² = 0
=> A².B².x² - (A² + B²).x + 1 = 0 [A, B ≠ 0]
=> A²B².x² - [(A + B)² - 2AB].x + 1 = 0
Putting A + B = - b/a & AB = c/a
(c/a)².x² - [(-b/a)² - 2.c/a].x + 1 = 0
=> (c²/a²).x² - [b²/a² - 2.c/a].x + 1 = 0
=> c².x² - (b² - 2ca).x + a² = 0
- This is the required equation.
Now, for the second part,
AB² = 1 => AB = 1/B => 1/B = c/a [as AB = c/a by (2)]
=> B = a/c
So, A = - B - b/a [ as A + B = -b/a by (1)]
=> A = - a/c - b/a = - (a² + bc)/(ac)
Putting A = - (a² + bc)/(ac) & B = a/c in (2)
[- (a² + bc)/(ac)].(a/c) = c/a
=> - (a³ + abc)/(ac²) = c/a
=> - (a³ + abc) = c³
=> a³ + c³ + abc = 0